(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The second part of the two-part study presents the tools and methods of chemical tracing, their classification, brief history and trends of development of dactyloscopic methods of detection. Methodology: The study synthesizes some of the most important technical handbooks and dozens of articles, published in the last decades. It also presents the author’s own research results published previously. Findings: The so-called chemical enhancement methods of latent print development are still developing to this day. Amino acid reagents have been evolving since the 1950s, some reagents have not stood the test of time, and some are still widely used today. Silver nitrate in its original form has become obsolete, but the next generation, the physical developer (PD) is widespread, and the more further generations: MMD and SMD methods are promising. Most of the electrochemical methods are currently only in the experimental stage. Value: In the Hungarian literature, such a comprehensive review has not been published on this subject for a long time.